Non-Covalent organocatalysis utilizing thiourea derivatives : understanding and creating organocatalyzed reactions - Hof, Kira; Justus Liebig University Giessen (My University, 2014)
The topic of this doctoral thesis is the non-covalent organocatalysis with thiourea derivatives. After a review of the worldwide achieved best results in the field of asymmetric organocatalysis with thiourea derivatives our already published results on the mode of action of the bis(trifluoromethyl)phenyl group in thiourea organocatalysts are shown. The also already published studies on the conformation of an Evans auxiliary with tin(IV) tetrachloride follow. The further chapters present our efforts to highlight the mechanism of the organocatalytic alcoholysis of styrene oxides, a non-catalyzed Passerini reaction as well as the synthesis of 1,4-dioxepins catalyzed by a thiourea derivative. In the last chapters we show our attempts toward the realization of an organocatalytic Sharpless dihydroxylation , towards the synthesis of oxazolidinones catalyzed by thiourea derivatives and towards the development of an organocatalytic Prins reaction.

Das Thema dieser Doktorarbeit ist die nicht-kovalente Organokatalyse mit Thioharnstoff-Derivaten. Nach einer Übersicht der bislang weltweit erzielten besten Ergebnisse im Bereich der asymmetrischen Organokatalyse mit Thioharnstoff-Derivaten werden hier unsere bereits veröffentlichten Ergebnisse zur Wirkungsweise der Bis(trifluormethyl)phenyl-Gruppe in Thioharnstoff-Organokatalysatoren gezeigt. Die ebenso bereits veröffentlichten Studien zur Konformation eines Evans-Auxiliars mit Zinn(IV)-tetrachlorid schließen sich an. Die weiteren Kapitel präsentieren unsere Bestrebungen den Mechanismus der organokatalytischen Alkoholyse von Styroloxiden zu beleuchten, eine nicht-katalysierte Passerini-Reaktion sowie die durch ein Thioharnstoff-Derivat katalysierte Synthese von 1,4-Dioxepinen. In den letzten Kapiteln zeigen wir unsere Versuche zur Realisierung einer organokatalytischen Sharpless-Dihydroxylierung , zur Synthese von Oxazolidinonen katalysiert durch Thioharnstoff-Derivate und zur Entwicklung einer organokatalytischen Prins-Reaktion.
Nicht-kovalente Organokatalyse unter Verwendung von Thioharnstoff-Derivaten : Organokatalytische Reaktionen verstehen und entwerfen
Keywords: Organokatalyse; Thioharnstoff; organocatalysis; thiourea; ddc:540